Metacognitive Monitoring and Control in Children's Prospective Memory. Issue 4 (8th August 2021) - Cottini, Milvia; Basso, Demis; Pieri, Alessandro; Palladino, Paola
ABSTRACT: This study investigated developmental differences in metacognitive monitoring and control in younger (5- to 6-year-old) and older (8- to 10-year-old) children's prospective memory (PM). Metacognitive monitoring was assessed by asking the children to judge their performance before (prediction) and after (postdiction) performing a resource-demanding event-based PM task. Metacognitive control was evaluated by comparison of ongoing task (OT) performance without and with the embedded PM task (i.e., attentional monitoring costs). Older children outperformed younger children in the PM task and were also more accurate in judging their PM performance than younger children, who greatly overestimated their PM performance. Attentional monitoring costs were found only in older children and were associated with both PM performance and performance predictions, thus suggesting that only older children were able to translate metacognitive monitoring into effective control. This study reports new findings on the relation between metacognition and PM during childhood.